Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the problem, we need to generate the first five terms of the arithmetic sequence defined by the given recursive formula:
1. Starting Term (Initial Condition): The first term is provided as [tex]\( f(1) = 54 \)[/tex].
2. Recursive Formula: The formula that defines each term based on the previous term is [tex]\( f(n) = f(n-1) - 9 \)[/tex].
Let's determine each term step by step:
- Step 1: The first term [tex]\( f(1) \)[/tex] is given as 54.
[tex]\[ f(1) = 54 \][/tex]
The sequence now is: [tex]\( [54] \)[/tex].
- Step 2: To find the second term [tex]\( f(2) \)[/tex], we use the recursive formula with [tex]\( n = 2 \)[/tex]:
[tex]\[ f(2) = f(1) - 9 = 54 - 9 = 45 \][/tex]
The sequence now is: [tex]\( [54, 45] \)[/tex].
- Step 3: To find the third term [tex]\( f(3) \)[/tex], we use the recursive formula with [tex]\( n = 3 \)[/tex]:
[tex]\[ f(3) = f(2) - 9 = 45 - 9 = 36 \][/tex]
The sequence now is: [tex]\( [54, 45, 36] \)[/tex].
- Step 4: To find the fourth term [tex]\( f(4) \)[/tex], we use the recursive formula with [tex]\( n = 4 \)[/tex]:
[tex]\[ f(4) = f(3) - 9 = 36 - 9 = 27 \][/tex]
The sequence now is: [tex]\( [54, 45, 36, 27] \)[/tex].
- Step 5: To find the fifth term [tex]\( f(5) \)[/tex], we use the recursive formula with [tex]\( n = 5 \)[/tex]:
[tex]\[ f(5) = f(4) - 9 = 27 - 9 = 18 \][/tex]
The sequence now is: [tex]\( [54, 45, 36, 27, 18] \)[/tex].
Thus, the first five terms of the sequence are:
[tex]\[ 54, 45, 36, 27, 18 \][/tex]
Given the choices:
1. [tex]\( 54, 63, 72, 81, 90 \)[/tex]
2. [tex]\( 45, 36, 27, 18, 9 \)[/tex]
3. [tex]\( 45, 54, 63, 72, 81 \)[/tex]
4. [tex]\( 54, 45, 36, 27, 18 \)[/tex]
The correct answer is:
[tex]\[ 54, 45, 36, 27, 18 \][/tex]
So, the correct choice is the fourth option.
1. Starting Term (Initial Condition): The first term is provided as [tex]\( f(1) = 54 \)[/tex].
2. Recursive Formula: The formula that defines each term based on the previous term is [tex]\( f(n) = f(n-1) - 9 \)[/tex].
Let's determine each term step by step:
- Step 1: The first term [tex]\( f(1) \)[/tex] is given as 54.
[tex]\[ f(1) = 54 \][/tex]
The sequence now is: [tex]\( [54] \)[/tex].
- Step 2: To find the second term [tex]\( f(2) \)[/tex], we use the recursive formula with [tex]\( n = 2 \)[/tex]:
[tex]\[ f(2) = f(1) - 9 = 54 - 9 = 45 \][/tex]
The sequence now is: [tex]\( [54, 45] \)[/tex].
- Step 3: To find the third term [tex]\( f(3) \)[/tex], we use the recursive formula with [tex]\( n = 3 \)[/tex]:
[tex]\[ f(3) = f(2) - 9 = 45 - 9 = 36 \][/tex]
The sequence now is: [tex]\( [54, 45, 36] \)[/tex].
- Step 4: To find the fourth term [tex]\( f(4) \)[/tex], we use the recursive formula with [tex]\( n = 4 \)[/tex]:
[tex]\[ f(4) = f(3) - 9 = 36 - 9 = 27 \][/tex]
The sequence now is: [tex]\( [54, 45, 36, 27] \)[/tex].
- Step 5: To find the fifth term [tex]\( f(5) \)[/tex], we use the recursive formula with [tex]\( n = 5 \)[/tex]:
[tex]\[ f(5) = f(4) - 9 = 27 - 9 = 18 \][/tex]
The sequence now is: [tex]\( [54, 45, 36, 27, 18] \)[/tex].
Thus, the first five terms of the sequence are:
[tex]\[ 54, 45, 36, 27, 18 \][/tex]
Given the choices:
1. [tex]\( 54, 63, 72, 81, 90 \)[/tex]
2. [tex]\( 45, 36, 27, 18, 9 \)[/tex]
3. [tex]\( 45, 54, 63, 72, 81 \)[/tex]
4. [tex]\( 54, 45, 36, 27, 18 \)[/tex]
The correct answer is:
[tex]\[ 54, 45, 36, 27, 18 \][/tex]
So, the correct choice is the fourth option.
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.